Policies for Educational Inclusion in Latin America: a Review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the publications made in high impact journals indexed inScopus database regarding the implementation of policies for Educational Inclusion in LatinAmerica during the period between 2015 and 2020. The information was identified through theapplication of search filters in the aforementioned platform, and organized by means of tables andfigures that allow the realization of a quantitative analysis of the information where maincharacteristics such as year of publication, country of origin, area of knowledge and type ofpublication are mentioned. The total number of publications is 986 documents, Brazil is identifiedas the Latin American country with the highest number of publications, a total of 482 documents,and the year with the highest number of publications in the period was 2020, when 245 researchworks were registered. The area with the highest number of contributions to the execution ofresearch projects related to the topic under study was Social Sciences with a total of 554 documentsand the type of publication chosen by most authors was the journal paper, which represents 76% ofthe total production. Similarly, examples of publications are identified to establish the position ofthe main authors regarding the management of policies to implement inclusive inclusion strategiesin Latin American academic institutions.